Management of physical illness in mental health services - Becker, T.; Blankenhorn, D.; Kilian, R. (Die Psychiatrie, 2012)
There is excess morbidity and mortality from physical illness in people with mental disorders. Problems of somatic care in this patient group comprise difficulties of access to care, problems of equity and adequate use of diagnostic procedures and interventions. There are deficits in routine screening and monitoring, e.g. of metabolic and cardiovascular risks. Measures to ensure adequate physical health care include practical steps to increase service uptake and screening, service-level change such as integrated care models, preventive health interventions and optimisation of psychotropic drug treatment to reduce risk profiles. Issues of stigma and discrimination are important, and the level of staff training and quality of professionals are likely to be pivotal in bringing about change.
Keywords: Severe mental illness; physical health care; lifestyle interventions